Disaster Awareness, Management Practices and Community Resilience in Tanauan City: An Explanatory Sequential Analysis for Policy Review - Fruelda, Emer John; Landicho, Jenald Joyce; Mabilangan, Johanah Irene (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined disaster awareness, disaster management practices, and community resilience among residents of Tanauan City, Batangas in relation to typhoon-related hazards. Anchored on Community Resilience Theory, Community-Based Disaster Risk Management Theory, the Protective Action Decision Model, and the Sendai Framework for Disaster Risk Reduction, the study used a sequential explanatory mixed-method design. The quantitative phase employed a descriptive-correlational approach involving 399 residents selected from urban and rural barangays, while the qualitative phase used a phenomenological approach with 10 to 15 selected participants. Data were gathered through a researcher-developed questionnaire with an open-ended interview section, validated by experts and pilot-tested for reliability. Findings showed that respondents demonstrated high levels of disaster awareness, disaster management practices, and community resilience. Disaster awareness and disaster management practices had strong and significant positive relationships with community resilience, with disaster management practices exerting a stronger influence than awareness alone. No significant differences were found when respondents were grouped according to sex, age, educational attainment, and length of residency. Qualitative findings explained that lived disaster experiences, community cooperation, institutional support, and the role of the Bureau of Fire Protection strengthened preparedness, response, and resilience, although gaps remained in evacuation behavior, technical response skills, equipment, manpower, logistics, and coordination. The study concluded that resilience in Tanauan City is shaped by both knowledge and action, and recommended stronger inter-agency coordination, disaster education, drills, volunteer programs, response monitoring, hazard mapping, equipment audits, and community feedback systems. The study supports SDG 11, SDG 16, and SDG 17 by promoting safer communities, stronger institutions, and coordinated disaster response partnerships. Its sustainability impact lies in strengthening community preparedness, governance, public safety, institutional coordination, and socio-economic recovery in a typhoon-prone locality.